Effectiveness of parents kiss for removal of pediatric nasal foreign bodies - Mir, Yaseer Ahmad; Khan, Mehraj Uid-din; Ayoub, Touseef Ul (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Background: Lodging of foreign body in the nose is one of the common accidents in pediatric age group leading to emergency consultation. Our aim was to evaluate the efficacy of mouth to mouth blowing to remove or facilitate removal of nasal foreign body. Methods: This was a prospective interventional study on 46 children aged 2-6 years presenting to pediatric emergency department at Sher- I-Kashmir institute of medical sciences with a history of unilateral foreign body in nose, between February 2016 and January 2019. At the most, three attempts of Mouth-to-mouth blows were given to remove the foreign body. In case of failure, instrumentation was used. The data was tabulated according to age, Gender, type of foreign body and management received. Results: Out of 46 children, 16 of the children were girls and 30 were boys. Parents kiss was successful in removing nasal foreign body in 34 (79.31%) children. Beads were the most common types of foreign bodies (36.96%). The most common presentation was report of accidental placement of something in the nose, other presentations were bleeding from the nose and unilateral discharge. 22 of 27 (81.48%) ‘Simple’ foreign bodies were removed by parents kiss while 12 of 19 (63.15%) ‘complex’ foreign bodies were removed by parents kiss. Conclusions: For children presenting with foreign body in the nose, mouth to mouth blowing should be the first maneuverer to facilitate removal.